Improving Students’ Vocabulary By Using Word Game Application To The First Grade at SMP N 3 Juli - Maulidia, Afifah; M. Afrizal (Journal of English Education and Social Science, 2024)
This research is entitled "Improving The Students' Vocabulary By Using Word Game Application To The First Grade At SMP N 3 Juli (Collaborative Classroom Action Research). The researcher raised the problems of this research, namely: first, how does the Wordwall vocabulary game application increase students' vocabulary? And secondly, how do students respond to the implementation of the Wordwall vocabulary game application at SMP N 3 Juli? The purpose of this research is to see the improvement and response of students to the application of the Wordwall vocabulary game application as a medium for learning Vocabulary skills. The method used in this research is Collaborative Classroom Action Research. Researchers collaborated with teachers at SMP N 3 Juli. The instruments used in this research were tests, observation sheets, and questionnaires. It can be seen that the average student speaking test score in the first cycle was 51.79% and in the second cycle it increased to 73.47%. The average value of student observations in cycle I was 56.6% and in cycle II was 86.4%. Students' responses to the application of the Wordwall vocabulary game application obtained an average score of 83.95. These results indicate that the application of the Wordwall vocabulary game in improving students' vocabulary achievement obtained good results and satisfactory responses. Thus this research is said to be successful